1993
DOI: 10.1002/pola.1993.080311016
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of [o‐(trimethylgermyl)phenyl] acetylene and polymer characterization

Abstract: [o‐(Trimethylgermyl)phenyl]acetylene was polymerized in the presence of WCl6, W(CO)6‐hv, etc., to give polymers whose weight‐average molecular weights reached ca. 7.0 X 105 at the highest. When the MoOCl4‐n‐Bu4Sn‐EtOH (1 : 1 : 1) catalyst was used, the polydispersity ratio of the polymer obtained was 1.08, and the number‐average molecular weight increased in direct proportion to monomer conversion; these indicate that this polymerization is a living polymerization. The polymer had the structure  [CHC(C6H4‐o‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 13 publications
1
26
0
Order By: Relevance
“…This upper bound which is showing a tradeoff between permeability and selectivity represents the biggest challenge for improved separation performance, and limit their application in industry [8,12]. From 1990 to 2008 different researchers have focused their efforts on tailoring polymer structures for membrane materials and obtained better separation of O 2 /N 2 [13,14], CO 2 /N 2 [15,16] and H 2 /N 2 [17,18]. Inspite of the improvement in gas separation properties it has only slightly shifted the upper bound as shown by Robeson in his revised upper bound in 2008 [19].…”
Section: Introductionmentioning
confidence: 98%
“…This upper bound which is showing a tradeoff between permeability and selectivity represents the biggest challenge for improved separation performance, and limit their application in industry [8,12]. From 1990 to 2008 different researchers have focused their efforts on tailoring polymer structures for membrane materials and obtained better separation of O 2 /N 2 [13,14], CO 2 /N 2 [15,16] and H 2 /N 2 [17,18]. Inspite of the improvement in gas separation properties it has only slightly shifted the upper bound as shown by Robeson in his revised upper bound in 2008 [19].…”
Section: Introductionmentioning
confidence: 98%
“…Several Ge-containing polyacetylenes have been synthesized thus far, and it has been revealed that some of them also show high gas permeability. For example, the oxygen permeability coefficients (P O 2 ) of poly[o-(trimethylgermyl)phenylacetylene] 5 and poly[1-phenyl-2-[m-(trimethylgermyl)phenylacetylene] 6 are 110 and 1100 barrer, respectively. Further, a patent 7 has disclosed that 1-(trimethylgermyl)-1-propyne (TMGP) polymerizes with TaCl 5 to produce a polymer that is insoluble in any solvent except carbon disulfide and whose P O 2 value is higher than 4000 barrer.…”
Section: Introductionmentioning
confidence: 99%
“…[62,75,81,87] The stability enhancement was reported to be especially significant if PPhA was substituted in the ortho position, i.e., in the vicinity to the polymer main chain. [81,87] The above discussion on the interconnection of cis-to-trans isomerization and degradation of PdFPhA and PPhA lead to the conclusion that the degradation proceeded (predominantly) as a consecutive process to cis-to-trans isomerization. Thus, the decrease in the rate of cis-to-trans isomerization of PdFPhA (compared to PPhA, Figure 7) evidently positively affects also the MW stability of PdFPhA.…”
Section: Discussionmentioning
confidence: 99%